Preparation method and application of artemisia desertorum emulsion

The Artemisia granulated emulsion prepared by sonication and high shear emulsification treatment solved the problems of poor solubility of Artemisia granulated in water and insufficient emulsification performance, significantly improved the performance of the dough products and reduced the use of Artemisia granulated.

CN119817611APending Publication Date: 2025-04-15ZHENGZHOU UNIVERSITY OF LIGHT INDUSTRY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411946304.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Artemisia sarcoidae has poor solubility in water and weak emulsification performance, resulting in a decrease in elongation in the dough and insufficient moisture distribution ability, affecting the taste of the dough products.

Method used

By mixing the Arborista gel powder with pure water and sonicating it, a "semi-solid oil" Arborista gel solution with a mass fraction of 0.7%-1.5%, then mixing it with soybean oil, and undergoing high shear emulsification treatment to prepare a "semi-solid oil" Arborista gel emulsion (ASKG-E).

Benefits of technology

The emulsification activity and state stability of the artemisia grease are improved, the elasticity, hardness, aging characteristics and anti-freeze cracking properties of the dough products are increased, and the amount of artemisia grease is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119817611A_ABST
    Figure CN119817611A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of food additives, and particularly discloses a preparation method and application of artemisia desertorum latex. The preparation method comprises the following steps: firstly, mixing artemisia seed gum powder with purified water in a centrifugal tube, swelling, and then carrying out ultrasonic treatment to prepare an artemisia seed gum solution with the mass fraction of 0.7-1.5%; and then mixing the artemisia glue solution with soybean oil, the addition amount of which is 4-12% of the total mass fraction, and emulsifying by adopting a high-shear emulsifying machine to prepare the artemisia glue emulsion. According to the present invention, the excellent content ratio of the artemisia desertorum gum to the soybean oil is obtained through the characterization measurement of the prepared artemisia desertorum gum emulsion, and the prepared artemisia desertorum gum emulsion is used in the flour product so as to significantly improve the performance of the flour product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of food additives, and particularly relates to a method for preparing artemisia sphaerocarpa latex and application thereof. Background Art

[0002] Artemisia sphaerocephala Krasch. gum (ASKG) is a natural plant polysaccharide extracted from Artemisia sphaerocephala seeds. [1] It has the characteristics of good water absorption (it can absorb 60 times its own weight of water), high viscosity (the viscosity is 1,800 times that of gelatin), good film-forming ability and biodegradability. It is widely used in food, biomedicine, chemical industry, environment and agriculture. However, ASKG is insoluble in water, distributed in a swollen state in water, and has weak emulsification properties.

[0003] ASKG can improve dough properties, so it is often added to wheat flour to take advantage of its bonding and complexing ability and fiber skeleton strengthening effect. ASKG can improve the gelatinization properties of dough, but due to the poor water solubility of ASKG, while strengthening the gluten network, the dough extensibility will decrease and the moisture distribution ability is weak. ASKG can restrain the extension of gluten protein, but excessive addition will compete with starch and gluten protein for water, hinder the formation of the gluten network, and thus affect the taste of pasta products. Therefore, how to improve the water solubility of artemisia gum and reduce the amount of addition to improve dough extensibility needs to be explored.

[0004] Lipids have a very important effect on dough quality. The addition of lipids will change the physical and chemical properties of dough. Adding oils during the dough making process will form an oil film to wrap starch and protein macromolecules, limit the water absorption capacity of starch, improve the swelling of gluten protein, and improve the extensibility and air retention of dough. The addition of soybean oil has a great influence on the properties of dough. When the addition amount is low, it can increase the cross-linking degree of gluten protein and enhance the strength of gluten protein. As the addition amount increases, the elasticity of the dough can be increased, but the ordered structure of starch will decrease with the increase of the addition amount.

[0005] The existing treatment methods to improve the emulsification of Artemisia sphaerocephala gum are mainly carboxymethylation, enzymatic treatment, and preparing emulsified Artemisia sphaerocephala gum by high-pressure homogenization of Artemisia sphaerocephala gum and oil. The literature [Wei Xiaoyi, Si Xiaojing, Cui Linlin, et al. Carboxymethylation and emulsified Artemisia sphaerocephala gum on the gluten-enhancing effect of wheat flour [J] is to improve the water solubility and emulsification through carboxymethylation and oil-based emulsification. Among them, carboxymethylation is a chemical modification. If it is added to food as a food additive, it will affect food safety. In addition, this modification method only works on the gluten-enhancing effect of wheat flour. The other oil-based modification of Artemisia sphaerocephala gum only works on oil-based dough. After modification, its storage stability is poor and it needs to be prepared and used immediately, which brings inconvenience to food production. Summary of the invention

[0006] At present, the wormwood gum added to flour products is mostly in powder form, which can easily cause uneven mixing and competition for water. In view of these problems, the solid powder of wormwood gum is now prepared into a liquid state, but the ordinary wormwood gum solution has poor solubility and is unstable. Therefore, the present invention provides a method for preparing a "semi-solid oil" wormwood gum emulsion (named ASKG-E) and applies it to flour products. It is found that its emulsifying activity and state stability are improved, and it is added to the dough to improve the elasticity, hardness, aging characteristics, anti-freeze cracking and other properties of the flour products, and the amount of wormwood gum added is reduced under the same improvement effect on the flour products.

[0007] The solution adopted by the present invention to solve the technical problem is: a method for preparing artemisia sphaerocephala latex, comprising the following steps:

[0008] S1. Preparation of Artemisia sphaerocephala gum solution: mixing Artemisia sphaerocephala gum powder and purified water in a centrifuge tube, and then ultrasonically treating the mixture to prepare an Artemisia sphaerocephala gum solution with a mass fraction of 0.7%-1.5%;

[0009] S2. Preparation of artemisia gum latex: mixing the artemisia gum solution with soybean oil, wherein the soybean oil is added in an amount of 4%-12% of the total mass fraction, and then subjecting the mixture to high shear emulsification treatment to prepare the artemisia gum latex.

[0010] In the above-mentioned method for preparing artemisia gum latex, the content of functional artemisia gum polysaccharide in the artemisia gum powder in step S1 is 80-83%, and the protein content is 3.7-5.5%.

[0011] In the above-mentioned method for preparing the artemisia gum emulsion, in step S1, the artemisia gum solution is ultrasonically treated in an ultrasonic device with a power of 160-480W and a frequency of 25kHz for 10 minutes, and stored at 25°C for 12 hours.

[0012] In the above-mentioned method for preparing the artemisia gum latex, in step S1, the artemisia gum solution is ultrasonically treated in an ultrasonic device with a power of 400 W and a frequency of 25 kHz for 10 minutes.

[0013] In the above-mentioned method for preparing the artemisia gum emulsion, the mass fraction of the artemisia gum solution is 0.9%, and the added amount of soybean oil is 6% of the total mass fraction.

[0014] In the above-mentioned method for preparing artemisia gum latex, the high shear emulsification treatment in step S2 is carried out by using a high shear emulsifier at a speed of 10000-12000 r / min in an intermittent treatment mode of treating for 1 minute and stopping for 30 seconds for a total treatment of 2-3 minutes.

[0015] The present invention also provides application of the artemisia sphaerocephala latex prepared by the preparation method in flour products.

[0016] The application of the above-mentioned Artemisia sphaerocephala latex in flour products improves the emulsification activity and stability of the Artemisia sphaerocephala latex, affects the water absorption, gluten properties and stability of the dough, thereby improving the elasticity, hardness, aging characteristics and frost crack resistance of the flour products.

[0017] The application of the above-mentioned Artemisia sphaerocephala gum latex in flour products can reduce the usage of Artemisia sphaerocephala gum while ensuring the performance of the dough.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] 1. The present invention can destroy the glycosidic bond of the wormwood gum solution by ultrasonic treatment, reduce the molecular weight, and form a loose fragmented structure. The smaller-sized polysaccharide has a higher water mobility and thus has a higher two-phase interface capacity. When the high shear machine shears and mixes the wormwood gum and oil, a tighter interface layer can be formed, which helps to stabilize the oil droplets and promote the activity and stability of the emulsion.

[0020] 2. The artemisia latex prepared by the present invention has a "semi-solid oil" texture as a whole, has stable performance, does not delaminate during long-term storage, does not need to be prepared as needed, and is more convenient to use.

[0021] 3. The artemisia gum emulsion prepared by the present invention can maintain good properties of dough such as water absorption rate, stability time and cooking stability with less artemisia gum added; and after being added to the noodle products for freezing, it can effectively improve the freezing quality of the noodle products.

[0022] 4. The preparation method of the Artemisia sphaerocephala latex of the present invention is a physical preparation process, which does not require the participation of chemical reagents throughout the process, has no risk of chemical reagent residues, and is relatively safer to add to food. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Emulsifying properties of Artemisia sphaerocephala latex prepared with different mass fractions of ASKG.

[0024] Figure 2 Emulsifying properties of Artemisia sphaerocephala latex prepared with different soybean oil addition amounts.

[0025] Figure 3 The effect of different ASKG mass fractions on the particle size of ASKG-E.

[0026] Figure 4 The effect of different soybean oil addition amounts on the particle size of ASKG-E.

[0027] Figure 5 The effect of different ASKG mass fractions on the Zeta potential of ASKG-E.

[0028] Figure 6The effect of different soybean oil addition amounts on the Zeta potential of ASKG-E.

[0029] Figure 7 Microscope observation of Artemisia sphaerocephala latex prepared with different mass fractions of ASKG.

[0030] Figure 8 Microscope observation of Artemisia sphaerocephala rubber emulsion prepared with different soybean oil addition amounts.

[0031] Fig. 9 Effects of different ASKG mass fractions on the rheological properties of ASKG-E.

[0032] Fig.10 Effects of different soybean oil addition amounts on the rheological properties of ASKG-E. DETAILED DESCRIPTION

[0033] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.

[0034] Example 1: This example provides a method for preparing an artemisia gum latex, and studies the properties and performance of the artemisia gum latex prepared with different mass fractions of artemisia gum and different mass fractions of soybean oil. The main contents are as follows.

[0035] 1. Materials and methods

[0036] (1) Materials and instruments

[0037] Artemisia sphaerocephala gum (ASKG) (polysaccharide content 82.8%, protein content 4.1%, ash content 0.72%), Shanghai Yuanye Biotechnology Co., Ltd.; soybean oil, refined wheat flour, purified water, commercially available.

[0038] A25 high shear emulsifier, Shanghai Ouhe Machinery Equipment Co., Ltd.; UV-2802 UV-visible spectrophotometer, Unico Shanghai Instrument Co., Ltd.; Malvern Mastersizer 3000 laser particle size analyzer, Zetasizer pro nanoparticle size and Zeta instrument, Malvern Instrument Co., Ltd., UK; EX21 biological microscope, Ningbo Sunny Instrument Co., Ltd.; MCR302e rotational rheometer, Anton Paar, Austria; Mixolab mixing experiment instrument, Chopin, France.

[0039] (2) Preparation method

[0040] First, different amounts of Artemisia sphaerocephala gum powder were weighed and mixed with pure water in a centrifuge tube to make the total mass of the solution 50 g; the mixture was ultrasonically treated for 10 min in an ultrasonic device (working parameters: power 400 W, frequency 25 kHz), and then stored at 25°C for 12 h to prepare Artemisia sphaerocephala gum solutions with mass fractions of 0.7%, 0.9%, 1.1%, 1.3% and 1.5%, respectively.

[0041] When preparing the Artemisia sphaerocephala latex, the experiment was conducted in two groups. In the first group, ASKG solutions of different mass fractions were mixed with soybean oil accounting for 6% of the total mass fraction, and the total mass of the emulsion was 50g. A high shear emulsifier was used to emulsify it, with a speed of 12000r / min, 60s of shearing each time, 30s of rest, and 3 cycles to prepare the "semi-solid oil" emulsion ASKG-E. During the sample shearing process, ice cubes were placed outside to prevent the sample temperature from being too high and causing qualitative changes.

[0042] The second group used an ASKG solution with a mass fraction of 0.9% mixed with soybean oil with a total mass fraction of 4%, 6%, 8%, 10% and 12%, respectively, and the preparation conditions were the same as the first group.

[0043] The characterization of different Artemisia sphaerocephala latex ASKG-E obtained from the first and second groups of tests included the following items:

[0044] Ⅰ. Emulsification

[0045] Emulsification performance is usually evaluated by EAI and ESI to characterize the ability of polysaccharide molecules to quickly adsorb on the surface of oil droplets to stabilize the oil-water interface and the ability of the formed emulsion to resist phase separation. This example refers to the method of Lv Jing et al. (Lv Jing, Yang Jieru, Zhu Jing, et al. Effects of different extraction methods on the structural properties and functional activity of walnut green peel pectin [J]. Grain and Oil) with slight modifications. Immediately at 0 min, 100 μL of the prepared emulsion was taken and mixed with 10 mL of 0.1 g / mL sodium dodecyl sulfate solution, and the absorbance was measured at a wavelength of 500 nm. After the emulsion was allowed to stand for 10 minutes, the absorbance was measured using the same method. The emulsifying activity index (EAI) and emulsifying stability index (ESI) of ASKG were calculated according to formulas (1) and (2).

[0046]

[0047] Where: B is the multiple of the interfacial area of ​​the emulsion relative to the turbidity, which is 2; Z is the value of ln10, which is 2.303; A 0 is the absorbance of the initial sample; N is the dilution factor (100); L is the width of the cuvette, cm; is the volume fraction of oil phase, %; ρ is the mass concentration of ASKG, g / mL; A 10 is the absorbance of the sample after standing for 10 minutes; △t is the time difference between two absorbance measurements, min.

[0048] The emulsification performance results of the Artemisia sphaerocephala latex ASKG-E prepared with different mass fractions of ASKG are shown in Figure 1 The emulsification performance results of Artemisia sphaerocephala latex with different soybean oil addition amounts are shown in Figure 2 shown.

[0049] Depend on Figure 1 It can be seen that under the same soybean oil mass fraction, with the increase of ASKG mass fraction, the emulsification effect of ASKG-E first increases and then decreases. When the mass fraction reaches 0.9%, the emulsification performance of ASKG-E is optimal, and the EAI and ESI at this time are 99.18m 2 / g, 40.54min, and the emulsification performance and stability of ASKG-E decreased rapidly as the mass fraction of ASKG continued to increase. The reason may be that with the increase of the mass fraction of ASKG, ASKG will aggregate more water, which is not conducive to the shear dispersion of oil droplets.

[0050] Depend on Figure 2 It can be seen that when the soybean oil addition reached 6%, the EAI and ESI of ASKG-E reached their peak values. As the soybean oil addition increased to 12%, the ESI of ASKG-E dropped to 76.39 m 2 / g, EAI dropped to 21.12min. This may be because the polypeptide chains contained in ASKG can form a solid gel network structure in the ASKG-E emulsion, thereby limiting the aggregation of oil droplets in the emulsion. However, as the amount of soybean oil added continued to increase, the network structure could not evenly adsorb the oil, resulting in the loss of the emulsification performance of the emulsion.

[0051] Ⅱ. ASKG-E average particle size and particle size distribution

[0052] The particle size of the emulsion can directly reflect the structure and aggregation degree of the emulsion. The average particle size of the emulsion is an important indicator for determining its stability. Generally, the smaller the average particle size of the emulsion, the more stable the emulsion. This embodiment refers to the method of LI et al. (LIX F, YANG SN, LU C, et al. Complexation of pea albumins with anionic polysaccharides and purification of PA1a[J]. Food hydrocolloids) and uses a laser particle size analyzer to measure the particle size of the emulsion. The refractive index is 1.46 for the sample and 1.33 for the aqueous phase, respectively. The volume average particle size d(4,3) is used to characterize the average particle size of the emulsion. The average particle size and particle size distribution of the artemisia gum latex ASKG-E prepared with different mass fractions of ASKG are shown in the figure. Figure 3 As shown in Figure 2, the average particle size and particle size distribution of Artemisia sphaerocephala latex with different soybean oil addition amounts are shown in Figure 2. Figure 4 shown.

[0053] Depend on Figure 3 (a) It can be seen that as the mass fraction of ASKG increases, the average particle size of ASKG-E decreases first and then increases. At 0.9%, the average particle size of ASKG-E is the smallest at 39.20 μm. Figure 3 (b) It can be seen that when the mass fraction of ASKG is 0.9%, ASKG-E presents a unimodal distribution with the narrowest distribution range. However, as the mass fraction of ASKG increases, the distribution of ASKG-E changes from a unimodal structure to a bimodal structure. This indicates that when the amount of ASKG is appropriate, the particles are completely applied to the oil-water interface, thereby forming a barrier, the interval between droplets becomes smaller, the particle size remains basically stable, and the distribution is uniform; when the mass fraction of ASKG is too large, the gel network structure formed by ASKG-E is denser, thereby increasing the probability of oil droplets colliding to form larger oil droplets, and it is difficult to form a relatively stable emulsion structure.

[0054] Depend on Figure 4 It can be seen that with the increase of soybean oil addition (6% to 12%), the average particle size of ASKG-E increased from 39.20μm to 58.81μm. ASKG-E has a unimodal distribution and the emulsion shifts toward larger particle sizes as the amount of soybean oil added increases. When the amount of soybean oil added reaches 12%, the particle size distribution area of ​​ASKG-E is the widest and the emulsification properties are unstable. This may be because as the amount of soybean oil added increases, ASKG is not enough to wrap all the oil droplets, resulting in an unstable emulsion system.

[0055] III. ASKG-E Zeta Potential

[0056] Referring to Zhang et al. (ZHANG S, HOLMES M, ETTELAIE R, et al. Pea protein microgel particles as Pickering stabilisers of oil-in-water emulsions: Responsiveness to pH and ionic strength [J]. Food hydrocolloids), the Zeta potential of the emulsion was determined using a nanoparticle size and Zata potential analyzer. After taking 100 μL of the sample to be tested and diluting it with 10 mL of ultrapure water, the sample was placed in a DTS1070 cuvette with an electrode, and the test conditions were set to a temperature of 25°C and an equilibrium time of 1 min. The Zeta potential of the Artemisia sphaerocephala latex ASKG-E prepared with different mass fractions of ASKG is shown in the figure. Figure 5 As shown in Figure 2, the ASKG-EZeta potential of Artemisia sphaerocephala latex with different soybean oil addition amounts is as follows: Figure 6 shown.

[0057] Depend on Figure 5 and Figure 6 It can be seen that when the mass fraction of ASKG is 0.9% and the amount of soybean oil added is 6%, the absolute value of the Zeta potential of ASKG-E (39.28mV) reaches its maximum value, and then the absolute value of the Zeta potential gradually decreases with the increase of the mass fraction of ASKG and the amount of soybean oil added. When ASKG-E carries more negative charges, the electrostatic repulsion in the particles increases, thereby increasing the repulsive force between particles and increasing the distance between particles, which better hinders the unstable aggregation of particles and enhances the stability of the emulsion.

[0058] Ⅳ. ASKG-E microstructure

[0059] The microstructure of the emulsion is often used to intuitively characterize the emulsification of the emulsion. In this example, 50 μL of the emulsion sample to be tested was dripped onto a glass slide. After the emulsion state was stable, the emulsion was observed at a focal length of 100× and photographed and analyzed using digital image analysis software. The microstructure of the Artemisia sphaerocephala latex ASKG-E prepared with different mass fractions of ASKG is shown in FIG. Figure 7 As shown in the figure; the microstructure of Artemisia sphaerocephala latex ASKG-E with different soybean oil addition amounts is shown in the figure Figure 8 shown.

[0060] Depend on Figure 7It can be seen that when the mass fraction of ASKG is 0.9%, the droplets of ASKG-E are small and uniform. At this time, the number of ASKG molecules covering the surface of the oil droplets increases, which can stabilize a larger interface area, prevent the aggregation of droplets, and form a tight and stable interface film. When the mass fraction of ASKG exceeds 0.9%, the droplet diameter of the emulsion increases, and the aggregation between droplets also increases significantly. The reason for this phenomenon may be that when the mass fraction of ASKG is too high, the ASKG molecules on the interface reach saturation, and the excess molecules cannot effectively participate in the stabilization of the droplets, resulting in an increase in the droplet diameter.

[0061] Depend on Figure 8 It can be seen that the effect of different soybean oil addition amounts on ASKG-E is particularly obvious. When the soybean oil addition amount is 4%, the oil phase volume is small, and the binding ability of oil droplets and water is weak, resulting in sparse distribution of ASKG-E droplets and the presence of larger particles. When the soybean oil addition amount is 6%, the ASKG-E particles are evenly distributed, small in size, and have strong electrostatic repulsion between molecules, making them more stable in subsequent processing and storage. However, as the amount of soybean oil added continues to increase (8% to 12%), ASKG-E experienced bridging, uneven distribution of droplets, and a large amount of coagulation. Larger droplets will weaken the electrostatic repulsion, increase the difficulty of water molecules to wrap them, and result in poor emulsion stability.

[0062] Ⅴ. Rheological properties of ASKG-E

[0063] The interfacial composition of the emulsion plays a crucial role in its rheological behavior. This example refers to the method of Liu Ning et al. (Liu Ning, Xue Xiaoting, Zhang Zhongfang, et al. Preparation of diglyceride emulsion by ultrahigh pressure treatment of sesame protein and study of its digestion and oxidation properties [J]. Journal of Shaanxi University of Science and Technology) and uses a rheometer to measure the rheological properties of the emulsion. The parallel plate fixture uses P / 50, the gap is set to 1mm, the temperature is 25°C, and 3.2mL of emulsion is taken into the fixture gap. The shear rate of the apparent viscosity is set to 0.1~200s -1 The scanning frequency range of dynamic rheology was set to 0.1-10 Hz, and the strain was fixed at 0.5%. The effect of different ASKG mass fractions on the rheological properties of Artemisia sphaerocephala latex ASKG-E is shown in Fig. 9 ; Effects of different soybean oil addition amounts on the rheological properties of Artemisia sphaerocephala latex ASKG-E Fig.10 .

[0064] Depend on Fig. 9(a) It can be seen that the apparent viscosity of ASKG-E first drops sharply and then gradually slows down with the increase of shear rate. This is because at a higher shear rate, the grid structure of the emulsion will be destroyed by the shear force, and the structure will be reorganized according to the shear direction, resulting in shear thinning, showing the characteristics of a non-Newtonian fluid. As the mass fraction of ASKG increases, the apparent viscosity of the corresponding ASKG-E system increases, which may be related to the water absorption capacity of ASKG. The higher the mass fraction of ASKG, the stronger the hydration capacity, and the emulsion changes from a flow state to a gel state, and the gel state gives it a high viscosity characteristic. Fig. 9 (b) It can be seen that with the increase of ASKG mass fraction, the storage modulus (G′) and loss modulus (G″) of the emulsion are also gradually increasing, among which G′ is always higher than G″, indicating that the formation of ASKG-E gel structure is dominated by elastic efficiency and shows typical solid elastic characteristics.

[0065] Depend on Fig.10 (a) It can be seen that the change trend of apparent viscosity during the entire emulsification process is Fig.10 The changes of G' and G" in (b) are consistent. As the amount of soybean oil added increases, the apparent viscosity of the ASKG-E system, G' and G" of the emulsion first increase and then decrease. The emulsified system is a thermodynamically unstable system, and it is necessary to add emulsifiers to adsorb on the surface of the oil droplets to prevent flocculation or aggregation between the oil droplets, thereby reducing the surface tension and maintaining the stability of the emulsion. Therefore, when the amount of artemisia gum in the system is constant, as the oil content increases, the artemisia gum changes from a state of complete adsorption of oil droplets to a state of incomplete adsorption, and bridging flocculation occurs, the stability of the emulsion is destroyed, and the apparent viscosity value, G' and G" show a phenomenon of first increasing and then decreasing. In addition, at different oil phase volumes, the G' of the emulsion is significantly higher than G", indicating that all samples exhibit obvious elastic behavior.

[0066] Based on the above test data, it can be seen that the artemisia gum emulsion prepared when the mass fraction of the artemisia gum solution is 0.9% and the soybean oil addition amount accounts for 6% of the total mass has uniform particle distribution, small volume, and significantly better emulsification activity and stability.

[0067] Example 2: This example studies the effect of different ultrasonic treatment conditions on the performance of Artemisia sphaerocephala gum emulsion. First, 6 portions of Artemisia sphaerocephala gum solutions with a mass fraction of 0.9% were prepared, each portion was 50 g; one group was not subjected to ultrasonic treatment as a blank control, and the other 5 groups were subjected to ultrasonic treatment for 10 minutes at powers of 160 W, 240 W, 320 W, 400 W, and 480 W, respectively, and a frequency of 25 kHz to obtain Artemisia sphaerocephala gum solutions.

[0068] Each group of prepared Artemisia sphaerocephala gum solution was mixed with 6% soybean oil, and the total mass of the emulsion was 50g. A high shear emulsifier was used to emulsify it, with a speed of 12000r / min, shearing for 60s each time, resting for 30s, and circulating 3 times to prepare the "semi-solid oil" emulsion ASKG-E.

[0069] The emulsification activity index, infusion particle size, ζ potential and emulsion stability index of the Artemisia sphaerocephala latex in different test groups were determined. The results are shown in Table 1 below.

[0070] Table 1 Performance test results of Artemisia sphaerocephala latex prepared with the assistance of different ultrasonic powers

[0071]

[0072] Note: The mean and standard error of three replicates are taken. Different superscript letters indicate significant differences at the P<0.05 level.

[0073] As can be seen from Table 1, when the ultrasonic power is 400W, the overall performance of the prepared Artemisia gum emulsion is significantly better, indicating that the ultrasonic power setting at 400W is conducive to the Artemisia gum emulsion to maintain good stability and emulsification activity. Although the Artemisia gum solution in the blank control group that was not ultrasonically treated can improve the stability of the emulsion after high shear treatment, its emulsification activity is significantly worse than that of other ultrasonic treatment groups. Ultrasonic action can reduce the size of emulsion droplets, inhibit aggregation and creaming between droplets, and increase the activity and stability of the emulsion. However, under excessive treatment, polysaccharides will form aggregates, reduce the interaction between polysaccharides and oils, destroy the balance between the hydrophobic and hydrophilic polymers of the polysaccharide-based emulsion, and make the emulsion unstable. Therefore, the selection of ultrasonic power has a great influence on the stability of the Artemisia gum emulsion.

[0074] Example 3: This example provides a method for preparing an artemisia gum emulsion. First, the artemisia gum powder and pure water are mixed in a centrifuge tube to fully swell. After mixing, the mixture is treated under an ultrasonic device for 10 minutes. The ultrasonic parameters are 400W and 25kHz to prepare an artemisia gum solution with a mass fraction of 0.9%. Then, the prepared artemisia gum solution is mixed with soybean oil. The soybean oil addition amount is 6% of the total mass fraction. A high shear emulsifier is used to emulsify it at a speed of 10,000 r / min and an emulsification time of 160s to prepare a "semi-solid oil" emulsion ASKG-E.

[0075] Example 4: In this example, the artemisia gum latex prepared in Example 3 was used in the preparation of noodles. At the same time, distilled water and artemisia gum solution were used for comparison to analyze the water absorption rate, breakage rate and texture of noodles in different test groups, as follows.

[0076] Test 1: Accurately weigh 200g of wheat flour and 80g of distilled water, knead the dough in a dough mixer for 10 minutes, let it rise at room temperature for 20 minutes, and then use a small electric dough press to roll it 6 times to form a dough sheet with a thickness of 2mm. After cutting and shortening, it forms noodles with a width of 3mm and a length of 200mm.

[0077] Test 2: Accurately weigh 200g of wheat flour and 80g of distilled water, add 0.05g of artemisia gum, knead the dough in a dough mixer for 10 minutes, let it rise at room temperature for 20 minutes, and then use a small electric dough press to roll it 6 times to form a dough sheet with a thickness of 2mm. After cutting and shortening, it forms noodles with a width of 3mm and a length of 200mm.

[0078] Test 3: Accurately weigh 200g of wheat flour and 74.2g of distilled water, add 5.8g of artemisia gum emulsion (equivalent to 0.05g of artemisia gum), knead the dough in a dough mixer for 10 minutes, let it rise at room temperature for 20 minutes, and then use a small electric dough press to roll it 6 times to form a dough sheet with a thickness of 2mm. After cutting and shortening, it forms noodles with a width of 3mm and a length of 200mm.

[0079] Test 4: Accurately weigh 200g of wheat flour and 75.5g of distilled water, add 4.5g of artemisia gum latex (equivalent to 0.04g of artemisia gum), knead the dough in a dough mixer for 10 minutes, let it rise at room temperature for 20 minutes, and then use a small electric dough press to roll it 6 times to form a dough sheet with a thickness of 2mm. After cutting and shortening, it forms noodles with a width of 3mm and a length of 200mm.

[0080] The water absorption, breaking rate and texture results are shown in Tables 2 and 3 below.

[0081] Measurement of water absorption:

[0082]

[0083] Where: M2 is the weight of noodles after cooking (g); M1 is the weight of noodles before cooking (g).

[0084] Measurement of broken noodles rate: Take 40 noodles of 20 cm in length, put them into boiling water and cook until there is no white core in the center of the noodles, take them out, and calculate the number of intact noodles, recorded as N. The specific formula is:

[0085]

[0086] Where: N is the number of complete noodles.

[0087] Table 2 Water absorption rate and breaking rate of noodles in different test groups

[0088]

[0089] Table 3 Texture analysis of noodles in different test groups

[0090]

[0091] As shown in Table 2, the breaking rate of noodles added with Artemisia sphaerocephala emulsion after steaming is 0%, while the breaking rate of noodles in the Artemisia sphaerocephala emulsion group is 5%, which means that Artemisia sphaerocephala emulsion improves the performance of noodles better than Artemisia sphaerocephala emulsion. As shown in Table 3, Artemisia sphaerocephala emulsion significantly improves the hardness and elasticity of noodles, reduces its hardness and chewiness, and increases its elasticity, cohesion and resilience. Therefore, adding Artemisia sphaerocephala emulsion is more suitable for producing noodles that require high ductility, such as stewed noodles and ramen noodles.

[0092] Example 4: In order to further verify the application effect of the Artemisia sphaerocephala latex prepared by the present invention in frozen noodle products, the Artemisia sphaerocephala latex prepared in Example 3 was used in the preparation of dumplings, and distilled water and Artemisia sphaerocephala latex were set as controls at the same time. The color difference and texture difference of the dumpling wrappers and dumplings in different test groups after freezing were analyzed, as follows.

[0093] Experiment 1: Accurately weigh 200g of wheat flour and 80g of distilled water, knead the dough in a dough mixer for 10 minutes, put the kneaded dough into a dough press, roll it for 6 times, and then seal it in a fresh-keeping bag. Let it stand at room temperature for 20 minutes and then continue to roll it for 3 times. Finally, control the thickness of the dough sheet to 2.0mm, use a dumpling wrapper mold to press it into a round dumpling wrapper with a diameter of 70mm, seal part of the dumpling wrapper in a fresh-keeping bag, and wrap the remaining part into dumplings, put them in a fresh-keeping bag, and store them in the freezer for 1 week, 3 weeks and 5 weeks.

[0094] Experiment 2: Accurately weigh 200g of wheat flour, add 0.05g of artemisia gum and 80g of distilled water, knead the dough in a dough mixer for 10 minutes, put the kneaded dough into a dough press, roll it for 6 times, and then seal it in a fresh-keeping bag. Let it stand at room temperature for 20 minutes and continue to roll it for 3 times. Finally, control the thickness of the dough to 2.0mm, use a dumpling skin mold to press it into a round dumpling skin with a diameter of 70mm, seal part of the dumpling skin in a fresh-keeping bag, and wrap the remaining dumpling skin into dumplings, put them in a fresh-keeping bag, and store them in the freezer for 1 week, 3 weeks and 5 weeks.

[0095] Experiment 3: Accurately weigh 200g of wheat flour, add 5.8g of artemisia gum emulsion (equivalent to 0.05g of artemisia gum mass), 74.2g of distilled water, knead the dough in a dough mixer for 10 minutes, put the kneaded dough into a dough press, roll it for 6 times and then seal it in a fresh-keeping bag, let it stand at room temperature for 20 minutes and continue to roll it for 3 times, finally control the thickness of the dough sheet to 2.0mm, use a dumpling skin mold to press it into a round dumpling skin with a diameter of 70mm, seal part of the dumpling skin in a fresh-keeping bag, and wrap the other part into dumplings in a fresh-keeping bag, and store them in the freezer for 1 week, 3 weeks and 5 weeks.

[0096] Experiment 4: Accurately weigh 200g of wheat flour, add 4.8g of artemisia gum emulsion (equivalent to 0.04g of artemisia gum), 75.2g of distilled water, and knead the dough in a dough mixer for 10 minutes. Put the kneaded dough into a dough press, roll it for 6 times, and then seal it in a fresh-keeping bag. After standing at room temperature for 20 minutes, continue to roll it for 3 times. Finally, control the thickness of the dough sheet to 2.0mm, and use a dumpling skin mold to press it into a round dumpling skin with a diameter of 70mm. Part of the dumpling skins are sealed in fresh-keeping bags, and the other part of the dumpling skins are used to wrap dumplings with fillings of the same type and quality, and stored in the freezer for 1 week, 3 weeks and 5 weeks.

[0097] The color difference of dumpling wrappers in different test groups after being frozen for 1 week, 3 weeks and 5 weeks was measured. The results are shown in Table 4.

[0098] Table 4 Color difference analysis results of dumpling wrappers in different experimental groups after 1 week, 3 weeks and 5 weeks of freezing

[0099]

[0100] From the color difference analysis of the dumpling skin after freezing for different times, it can be seen that: with the extension of freezing time, the L* values ​​of experimental groups 2, 3, and 4 are higher than those of the control group, and the artemisia gum emulsion group is better than the artemisia gum group. The reason may be that the ASKG molecular structure contains a certain amount of methoxy, acetyl and other lipophilic groups, which are combined with the oil phase through physical processing to further increase its emulsification properties, thereby preventing the oxidation of disulfide bonds and free thiol groups in the dough, and further preventing the deterioration of the frozen dough, making the skin smooth and delicate.

[0101] At the same time, the cracking rate and sensory scores of the frozen dumplings in different test groups were measured. The sensory scoring standards are shown in Table 5 and the results are shown in Table 6 below. The cracking rate formula is as follows:

[0102]

[0103] Table 5 Sensory evaluation scoring criteria for frozen dumplings

[0104]

[0105]

[0106] Table 6 Cracking rate and sensory scores of dumplings in different experimental groups at different freezing times

[0107]

[0108] From the data in Table 6, it can be seen that Artemisia gum and Artemisia gum emulsion improve the freeze-cracking rate and sensory quality of frozen dumplings after cooking, and the performance of dumplings made with Artemisia gum emulsion is better than that made with Artemisia gum. The reason may be that Artemisia gum emulsion improves the texture properties of the dumpling wrapper, such as viscosity, elasticity, hardness, adhesion, and cohesion, thereby reducing the freeze-cracking rate and improving the taste.

[0109] Example 5: In order to verify the effect of different amounts of Artemisia sphaerocephala emulsion added on the properties of non-fermented dough, this example is based on Example 4 and measures the water absorption, formation time, cooking stability, etc. of the dough prepared in different test groups. The results are shown in Table 7 below.

[0110] Table 7 Performance test results of dough prepared with different amounts of Artemisia sphaerocephala gum

[0111]

[0112] As can be seen from Table 7, the addition of ASKG and ASKG-E solutions will increase the water absorption rate, stability time and cooking stability of the dough compared with the blank group, while the formation time and weakening degree will be reduced, improving the processing performance of the dough, and the improvement effect of the ASKG-E group is better than that of the ASKG solution. The stability time reflects the shear resistance of the dough, and the weakening degree reflects the strength of the gluten structure. The smaller the weakening degree, the stronger the gluten strength. The ASKG and AKSG-E emulsion groups have longer stability times and stronger gluten network structures than the blank group. The reason may be that ASKG-E is easier to produce hydration reaction with starch in wheat flour after emulsification, thereby enhancing the stability time of the dough. The larger the cooking stability ratio, the stronger the cooking stability of the dough. The improvement of the cooking stability of the dough in the ASKG-E group may be due to the fact that some hydrophobic groups contained in the oil in the emulsion are combined with water molecules under the induction of ASKG after shearing, so that the emulsion is more fully combined with the dough. From the comparison between the groups with different amounts of artemisia gum added (0.05ASKG and 0.04ASKG-E), it can be seen that ASKG-E can achieve the same improvement effect with little difference in the water absorption rate, stability time and cooking stability of the dough when less artemisia gum is added.

[0113] Example 6: In this example, the Artemisia sphaerocephala gum emulsion prepared in Example 3 was used in the preparation of steamed bread. The purpose of the experiment was to verify the effect of Artemisia sphaerocephala gum emulsion with a small amount of Artemisia sphaerocephala gum on the quality of fermented flour products. The experiment was conducted by analyzing the texture of steamed bread in different test groups after being frozen for 1 week and then re-steamed. The specific implementation is as follows.

[0114] Test 1: Weigh 200g of flour, add 0.1g of yeast powder and 100g of distilled water, mix and stir for 12 minutes in a dough mixer to form a dough. Divide the dough into small pieces of 25g, knead them into round steamed buns, and place them in a constant temperature and humidity chamber (85% humidity, 37°C temperature) to rise for 40 minutes. Place the steamed buns in a steamer and steam for 20 minutes. After simmering for 5 minutes, take them out and cool for 1 hour, then place them in a sealed bag and package them. Then freeze them in a -20°C freezer for 1 week.

[0115] Test 2: Weigh 200g of flour, add 0.1g of yeast powder, 0.05g of Artemisia selengensis gum and 100g of distilled water, mix and stir in a dough mixer for 12 minutes to form dough. Divide the dough into small doughs of 25g, knead into round steamed buns and place in a constant temperature and humidity chamber (85% humidity, 37°C temperature) to rise for 40 minutes. Place the steamed buns in a steamer and steam for 20 minutes. After simmering for 5 minutes, take them out and cool for 1 hour, then place them in a sealed bag and package them. Then freeze them in a -20°C freezer for 1 week.

[0116] Test 3: Weigh 200g of flour, add 0.1g of yeast powder, 4.5g of Artemisia sphaerocephala latex (equivalent to 0.04g of Artemisia sphaerocephala latex) and 95.5g of distilled water, mix and stir in a dough mixer for 12 minutes to form dough. Divide the dough into small doughs of 25g, knead into round steamed buns and place in a constant temperature and humidity chamber (85% humidity, 37°C temperature) to rise for 40 minutes. Place the steamed buns in a steamer and steam for 20 minutes. After simmering for 5 minutes, take them out and cool for 1 hour, and package them in sealed bags. Then freeze them in a -20°C freezer for 1 week.

[0117] The texture of the steamed buns was measured after being frozen for one week. The results are shown in Table 8.

[0118] Table 8 Texture analysis of steamed bread after being frozen for one week

[0119]

[0120] As can be seen from Table 8, Artemisia gum and Artemisia gum emulsion improved the sensory quality of frozen steamed bread after re-steaming, and the performance of Artemisia gum emulsion was better than that of Artemisia gum, mainly manifested in the reduction of hardness and adhesion, and the increase of elasticity, cohesion and recovery. The reason may be that Artemisia gum itself has a strong ability to bind water molecules, and water molecules form a network structure through hydrogen bonds. The Artemisia gum emulsion further refines the water molecules due to the presence of the oil phase. Therefore, Experiment 3 maintained better quality at a smaller amount of Artemisia gum added; and the amount of Artemisia gum added in Experiment 3 was less than that in Experiment 2, but they had the same improvement on the dough, which further proved the effect of Artemisia gum emulsion on the quality of steamed bread when the amount of Artemisia gum added was reduced.

[0121] The above description is only a preferred embodiment of the present invention and does not limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing an Artemisia sphaerocephala latex, characterized in that: The following steps are involved: S1. Preparation of Artemisia sphaerocephala gum solution: mixing Artemisia sphaerocephala gum powder and purified water in a centrifuge tube, and then performing ultrasonic treatment to prepare an Artemisia sphaerocephala gum solution with a mass fraction of 0.7%-1.5%; S2. Preparation of Artemisia sphaerocephala gum latex: mixing the Artemisia sphaerocephala gum solution with soybean oil, wherein the soybean oil addition amount is 4%-12% of the total mass fraction, and after mixing, high shear emulsification treatment is performed to prepare the Artemisia sphaerocephala gum latex.

2. The method for preparing the Artemisia sphaerocephala latex according to claim 1, wherein: The functional Artemisia sphaerocephala polysaccharide content in the Artemisia sphaerocephala powder in step S1 is 80-83%, and the protein content is 3.7-5.5%.

3. The method for preparing the Artemisia sphaerocephala latex according to claim 2, wherein: The polysaccharide content in the wormwood gum powder is 82.8%, and the protein content is 4.1%, and the contents are calculated by mass fraction.

4. The method for preparing the Artemisia sphaerocephala latex according to claim 1, wherein: In step S1, the artemisia gum solution is ultrasonically treated in an ultrasonic device with a power of 160-480 W and a frequency of 25 kHz for 10 min, and stored at 25° C. for 12 h.

5. The method for preparing the Artemisia sphaerocephala latex according to claim 4, wherein: In step S1, the Artemisia sphaerocephala gum solution is ultrasonically treated in an ultrasonic device with a power of 400 W and a frequency of 25 kHz for 10 min.

6. The method for preparing the Artemisia sphaerocephala latex according to claim 1, wherein: The mass fraction of the artemisia gum solution is 0.9%, and the added amount of soybean oil is 6% of the total mass fraction.

7. The method for preparing the Artemisia sphaerocephala latex according to claim 1, wherein: In step S2, the high shear emulsification treatment is carried out by using a high shear emulsifier at a rotation speed of 10000-12000 r / min in an intermittent treatment mode of treating for 1 minute and stopping for 30 seconds for a total treatment of 2-3 minutes.

8. Use of the artemisia sphaerocephala latex prepared by the preparation method according to any one of claims 1 to 7 in flour products.

9. The use of the Artemisia sphaerocephala latex in flour products according to claim 8, characterized in that: The emulsifying activity and stability of the artemisia gum latex are improved, which affects the water absorption, gluten properties and stability of the dough, thereby improving the elasticity, hardness, aging characteristics and frost crack resistance of the flour products.

10. The use of the Artemisia sphaerocephala latex in flour products according to claim 8, characterized in that: The artemisia gum emulsion can reduce the usage of artemisia gum while ensuring the performance of dough.